SEKOLAH UMUM BERBASIS ISLAM DI SMA UNGGULAN Haf-Sa ZAINUL HASAN GENGGONG - Umi Fatimah; Izzatul Amaliah; Fitrianingsih (Universitas Sains dan Teknologi Komputer, 2022)
In Indonesia today we find many Islamic-based schools, not only Islamic with their madrasahs, but many religious educational institutions such as Christianity, Catholicism, Hinduism and Buddhism which have schools where religious values ​​form the basis. learning process. Along with the development of religious education in public schools, attention to madrasas or Islamic education in general has occurred since the Central Indonesian National Committee Working Committee (BPKNIP) in the post-independence period issued an edict and proposed education or teaching in mushollah, surau, mosques and madrasas to continue. and improved”. Madrasa in the form we know today literally comes from Arabic which means the same or equivalent to the Indonesian word